PENGARUH PEMANFAATAN SISTEM INFORMASI AKUNTANSI KEUANGAN DAERAH, KUALITAS SUMBER DAYA MANUSIA, DAN PENGAWASAN KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH ACEH - Rosmalita, Nova; Nadirsyah, Nadirsyah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
The research examines the influence of the use of regional financial accounting information system, quality of human resources and regional financial supervision on the quality of the Aceh Goverment financial report. The population in this study is SKPA of Aceh Province. The sampling technique used is simple random sampling. This study uses primary data which obtained through the questionnaire results. The data were colleccted 64 questionnaires from 32 SKPA. Data analysis using multiple linear regression. The results show that together, regional financial accounting information system, quality of human resources and regional financial supervision on the quality of the Aceh Goverment financial report. Partially, each independent variable is an regional financial accounting information system, quality of human resources and regional financial supervision affects the quality of the Aceh Goverment financial report